The student's behavior in relation to group activities in the university environment (Research, Society and Development, 2021)
In an academic environment, the formation of social groups within the classroom is common; the aim of the study is to analyze the academics’ behavior and how the variables influence on learning and social life. In addition to the bibliographic survey on the subject, 107 interviews were conducted with academics from public and private institutions. The main findings, regarding the degree of agreement, are that 17% already knew someone in the class before starting college; 83% mention that the relationship with their classmates is very good; 45% feel quite calm doing jobs and group activities; 44% prefer the work and activities to be in groups; however, 76%, sometimes, prefer to do the work and activities alone. On the other hand, 41% mention that the students in the classroom are united in carrying out works and activities; and 89% approve the use of new teaching technologies, such as lives and interactive classes. As a contribution of the study, the points of greatest influence on the behavior of students in the school environment and the possible problems that may occur are suggested.